2019
DOI: 10.1002/jia2.25391
|View full text |Cite
|
Sign up to set email alerts
|

High risk and low uptake of pre‐exposure prophylaxis to prevent HIV acquisition in a national online sample of transgender men who have sex with men in the United States

Abstract: Introduction Trans masculine people who have sex with cisgender (“cis”) men (“trans MSM”) may be at‐risk for HIV infection when they have cis MSM partners or share needles for hormone or recreational drug injection. Limited data are available characterizing indications and uptake of pre‐exposure prophylaxis (PrEP) in trans MSM. The aim of this study was to assess PrEP indication and uptake as a means of primary HIV prevention for adult trans MSM in the U.S. Methods Between November and December 2017, a nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 36 publications
0
39
2
2
Order By: Relevance
“…This is despite the fact that transgender women who have sex with men have a 49 times higher odds of living with HIV than other adults of reproductive age, globally [ 121 ]. No studies reported including transgender MSM, another at-risk, but largely invisible, group [ 122 , 123 ], nor other gender-diverse identities (i.e., non-binary people).…”
Section: Discussionmentioning
confidence: 99%
“…This is despite the fact that transgender women who have sex with men have a 49 times higher odds of living with HIV than other adults of reproductive age, globally [ 121 ]. No studies reported including transgender MSM, another at-risk, but largely invisible, group [ 122 , 123 ], nor other gender-diverse identities (i.e., non-binary people).…”
Section: Discussionmentioning
confidence: 99%
“…84.1% of participants had heard of PrEP [160] Race/ ethnicity c,d Survey of a Northern California consortium of individuals with recently acquired HIV (N = 122), the majority of whom were MSM (84%) and of minority racial/ethnic background (64%) A lack of PrEP awareness was noted in 69% of Black participants [161] Survey of Black individuals in the USA (N = 855)…”
Section: Years 69%mentioning
confidence: 99%
“…PrEP awareness among TGW was 4.7% [ 155 ] Survey of substance-using Black MSM and TGW in New York City ( N = 1673) b Only 18.2% of participants were aware of PrEP [ 156 ] Gender a,b Survey of women visiting safety net family planning clinics in Atlanta ( N = 500), of whom 47% were aged ≤ 28 years, 69% Black, and 12% Hispanic Only 19% of participants knew about PrEP before their visit [ 157 ] Assessment of women enrolled in an HIV study at Southern US sites ( N = 225), the majority of whom were Black (83%) Of the 72 participants who were PrEP-eligible, only 11% had previously heard of PrEP [ 158 ] Focus groups and interview of HIV-negative cis women visiting an STI clinic or emergency department in Chicago ( N = 370), the majority of whom were Black (83%) d Only 30% of participants had heard of PrEP before the survey. The only factor associated with hearing about PrEP was knowing someone on PrEP [ 159 ] Cross-sectional survey of HIV-negative cis women involved in the criminal justice system ( N = 125) Only 25% of participants were aware of PrEP [ 37 ] Survey of individuals attending family planning and sexual health clinics in Arizona, the majority of whom were women (65%) Women had lower prior awareness of PrEP than men [ 19 ] Survey of TGM who have sex with cis men ( N = 857) 84.1% of participants had heard of PrEP [ 160 ] Race/ethnicity c,d Survey of a Northern California consortium of individuals with recently acquired HIV ( N = 122), the majority of whom were MSM (84%) and of minority racial/ethnic background (64%) A lack of PrEP awareness was noted in 69% of Black participants [ 161 ] Survey of Black individuals in the USA ( N = 855) …”
Section: Awareness and Knowledge As A Barrier To Prep Uptakementioning
confidence: 99%
“…A recent online survey of 857 transmasculine individuals who have sex with men found that of those who were HIV-negative, 52.5% met PrEP indications and 33.3% reported lifetime PrEP use (21.8% current and 11.5% past). 11 In another recent study, of 439 transmasculine individuals who were eligible for PrEP, only 11% had received a PrEP prescription. 12 …”
Section: Introductionmentioning
confidence: 99%